A fine-grained arc-consistency algorithm for non-normalized constraint satisfaction problems - Arangú, Marlene; Salido, Miguel A. (Zielona Góra: Uniwersytet Zielonogórski)
Constraint programming is a powerful software technology for solving numerous real-life problems. Many of these problems can be modeled as Constraint Satisfaction Problems (CSPs) and solved using constraint programming techniques. However, solving a CSP is NP-complete so filtering techniques to reduce the search space are still necessary. Arcconsistency algorithms are widely used to prune the search space.
Keywords: constraint satisfaction problems; filtering techniques; consistency algorithms